Greater recalled pain and movement-evoked pain are associated with longer 400-m walk and repeat stair climb timein older adults: the study of muscle, mobility, and aging - Theresa Mau; Corey B. Simon; Haley N. Barnes; Megan Hetherington-Rauth; Scott R. Bauer; Elsa S. Strotmeyer; Nancy E. Lane; Michael C. Rowbotham; Ashley A. Weaver; Terri L. Blackwell; Yurun Cai; Nancy W. Glynn; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Paradigm shifts in indoor air quality: Insights from the 2025 Stanford forum on sustainable and healthy buildings - Milana Trounce; Darin Anderson; Liam Bates; Seema Bhangar; Rob Bolin; Wenhao Chen; Sabrina Chwalek; Scott Frank; Jason Hartke; Kazukiyo Kumagai; Georgia K Lagoudas; Erik Malmstrom; et al. (Building and Environment, 2026)

AI as a catalyst for synergistic gains in indoor air quality and energy efficiency - Milana Trounce; Darin Anderson; William Bahnfleth; Liam Bates; Seema Bhangar; Rob Bolin; Wenhao Chen; Sabrina Chwalek; Scott Frank; Jason Hartke; Kazukiyo Kumagai; Georgia Lagoudas; et al. (Building and Environment, 2026)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

A review of extremophilic microalgae: Impacts of experimental cultivation conditions for the production of antimicrobials - Kathryn L. Rinaldi; Gerusa N.A. Senhorinho; Corey A. Laamanen; John A. Scott (Algal Research, 2024)

Microalgal harvesting for biofuels – Options and associated operational costs - Samantha J. McGrath; Corey A. Laamanen; Gerusa N.A. Senhorinho; J. Ashley Scott (Algal Research, 2024)

Field-testing effectiveness of window markers in reducing bird-window collisions - Georgia J. Riggs; Christine M. Barton; Corey S. Riding; Timothy J. O’Connell; Scott R. Loss (Urban Ecosystems, 2023)

Impact of acute consumption of beverages containing plant-based or alternative sweetener blends on postprandial appetite, food intake, metabolism, and gastro-intestinal symptoms: Results of the SWEET beverages trial - Eva Almiron-Roig; Santiago Navas-Carretero; Gabriele Castelnuovo; Louise Kjølbæk; Ana Romo-Hualde; Mie Normand; Niamh Maloney; Charlotte A. Hardman; Charo E. Hodgkins; Hariklia Moshoyiannis; Graham Finlayson; Corey Scott; et al. (Appetite, 2023)

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

A case study comparison of a sulphuric acid plant with and without on-site low-grade heat recovery and repurposing - Shannon H. McLean; Jeff Chenier; Sari Muinonen; Kyle Moreau; Corey A. Laamanen; John Ashley Scott (The International Journal of Life Cycle Assessment, 2022)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Selection and re-acclimation of bioprospected acid-tolerant green microalgae suitable for growth at low pH - Sabrina Marie Desjardins; Corey Alfred Laamanen; Nathan Basiliko; John Ashley Scott (Extremophiles, 2021)

Gene flow and climate‐associated genetic variation in a vagile habitat specialist - Zachary G. MacDonald; Julian R. Dupuis; Corey S. Davis; John H. Acorn; Scott E. Nielsen; Felix A. H. Sperling (Molecular Ecology, 2020)
Previous work in landscape genetics suggests that geographic isolation is of greater importance to genetic divergence than variation in environmental conditions. This is intuitive when configurations of suitable habitat are a dominant factor limiting dispersal and gene flow, but has not been thoroughly examined for habitat specialists with strong dispersal capability. Here, we evaluate the effects of geographic and environmental isolation on genetic divergence for a vagile invertebrate with high habitat specificity and a discrete dispersal life stage: Dod's Old World swallowtail butterfly, Papilio machaon dodi . In Canada, P. m. dodi are generally restricted to eroding habitat along major river valleys where their larval host plant occurs. A series of causal and linear mixed effects models indicate that divergence of genome‐wide single nucleotide polymorphisms is best explained by a combination of environmental isolation (variation in summer temperatures) and geographic isolation (Euclidean distance). Interestingly, least‐cost path and circuit distances through a resistance surface parameterized as the inverse of habitat suitability were not supported. This suggests that, although habitat associations of many butterflies are specific due to reproductive requirements, habitat suitability and landscape permeability are not equivalent concepts due to considerable adult vagility. We infer that divergent selection related to variation in summer temperatures has produced two genetic clusters within P. m. dodi , differing in voltinism and diapause propensity. Within the next century, temperatures are predicted to rise by amounts greater than the present‐day difference between regions of the genetic clusters, potentially affecting the persistence of the northern cluster under continued climate change.

Correction to: CpG‑creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)

CpG-creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)
Mutations can occur throughout the virus genome and may be beneficial, neutral or deleterious. We are interested in mutations that yield a C next to a G, producing CpG sites. CpG sites are rare in eukaryotic and viral genomes. For the eukaryotes, it is thought that CpG sites are rare because they are prone to mutation when methylated. In viruses, we know less about why CpG sites are rare. A previous study in HIV suggested that CpG-creating transition mutations are more costly than similar non-CpG-creating mutations. To determine if this is the case in other viruses, we analyzed the allele frequencies of CpG-creating and non-CpG-creating mutations across various strains, subtypes, and genes of viruses using existing data obtained from Genbank, HIV Databases, and Virus Pathogen Resource. Our results suggest that CpG sites are indeed costly for most viruses. By understanding the cost of CpG sites, we can obtain further insights into the evolution and adaptation of viruses.

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

Comparative population genomics confirms little population structure in two commercially targeted carcharhinid sharks - Claudia Junge; Stephen C. Donnellan; Charlie Huveneers; Corey J. A. Bradshaw; Alexis Simon; Michael Drew; Clinton Duffy; Grant Johnson; Geremy Cliff; Matias Braccini; Scott C. Cutmore; Paul Butcher; et al. (Marine Biology, 2019)

Sonic Estimation of Elasticity via Resonance: A New Method of Assessing Hemostasis - F. Scott Corey; William F. Walker (Annals of Biomedical Engineering, 2016)

Emergent stability in a large, free‐flowing watershed - Jonathan W. Moore; Michael P. Beakes; Holly K. Nesbitt; Justin D. Yeakel; David A. Patterson; Lisa A. Thompson; Corey C. Phillis; Douglas C. Braun; Corinna Favaro; David Scott; Charmaine Carr-Harris; William I. Atlas (Ecology, 2015)
While it is widely recognized that financial stock portfolios can be stabilized through diverse investments, it is also possible that certain habitats can function as natural portfolios that stabilize ecosystem processes. Here we propose and examine the hypothesis that free‐flowing river networks act as such portfolios and confer stability through their integration of upstream geological, hydrological, and biological diversity. We compiled a spatially (142 sites) and temporally (1980–present) extensive data set on fisheries, water flows, and temperatures, from sites within one of the largest watersheds in the world that remains without dams on its mainstem, the Fraser River, British Columbia, Canada. We found that larger catchments had more stable fisheries catches, water flows, and water temperatures than smaller catchments. These data provide evidence that free‐flowing river networks function as hierarchically nested portfolios with stability as an emergent property. Thus, free‐flowing river networks can represent a natural system for buffering variation and extreme events.

Intermittent aeration affects the bioremediation potential of two red algae cultured in finfish effluent - Scott Caines; Juan A. Manríquez-Hernández; Jim Duston; Peter Corey; David J. Garbary (Journal of Applied Phycology, 2014)

FR-H3: a new QTL to assist in the development of fall-sown barley with superior low temperature tolerance - Scott P. Fisk; Alfonso Cuesta-Marcos; Luis Cistué; Joanne Russell; Kevin P. Smith; Stephen Baenziger; Zoltán Bedo; Ann Corey; Tanya Filichkin; Ildikó Karsai; Robbie Waugh; Patrick M. Hayes (Theoretical and Applied Genetics, 2013)

Effects of native and invasive species on stream ecosystem functioning - Susanna E. Scott; Corey L. Pray; Weston H. Nowlin; Yixin Zhang (Aquatic Sciences, 2012)

Podokinetic stimulation causes shifts in perception of straight ahead - John T. Scott; Corey A. Lohnes; Fay B. Horak; Gammon M. Earhart (Experimental Brain Research, 2011)

Modifier gene study of meconium ileus in cystic fibrosis: statistical considerations and gene mapping results - Ruslan Dorfman; Weili Li; Lei Sun; Fan Lin; Yongqian Wang; Andrew Sandford; Peter D. Paré; Karen McKay; Hana Kayserova; Tereza Piskackova; Milan Macek; Kamila Czerska; et al. (Human Genetics, 2009)

Temporal Effects of Impact on Articular Cartilage Cell Death, Gene Expression, Matrix Biochemistry, and Biomechanics - Roman M. Natoli; C. Corey Scott; Kyriacos A. Athanasiou (Annals of Biomedical Engineering, 2008)